BANK AIR SUSU IBU (ASI) DALAM PERSPEKTIF HUKUM ISLAM - Baiduri, Baiduri (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2017)
The Purpose of this paper is to know on the law of breast milk bank (ASI bank) in the perspective of Islamic law. The method used in this paper is descriptive and analysis methods. The conclusion that the existence of a breast milk bank is permissible in Islamic law perspective with the requirement that the storage of breast milk should be in accordance with health standards. In addition, in the process of storing breast milk should pay attention to the identity of the owner of breast milk so that the use of breast milk in the bank of breast milk does not eliminate the identity of descendants (nasab) of their users.